Insider, outsider or multiplex persona? Confessions of a digital ethnographer's journey in Translation Studies - Chuan Yu (JoSTrans: The Journal of Specialised Translation)
Much attention has been paid to online collaborative translation in the past three decades. Methodologically, how we examine various forms of translation practices and communities on the internet is a challenge. Whilst digital ethnography has been recognised as a feasible methodology, the ethnographer's positionality throughout the process of fieldwork is often overlooked in the Translation Studies context. In this paper, I present a confessional tale consisting of three vignettes foregrounding the challenges, doubts and anxieties that I have confronted while using digital ethnography to study a Chinese online translation community. My reflections proceed from an analysis based on an insider/outsider dichotomy to the realisation of an alternative perspective, the multiplex persona. I argue that in the digital space, the notion of a multiplex persona, which views subjectivity and positionality from a decentred, multiplex and multi-dimensional perspective, is more constructive in helping researchers understand where these dilemmas come from, why they emerge, and how negotiations between the ethnographers and their informants develop.